IDENTIFICATION OF BEST PRACTICES IN MANAGING BANKING HR MANAGEMENT IN THE ERA OF AUTOMATION: WHAT EVIDENCE SHOWS - Nenden Hendayani (INTERNATIONAL JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS (INJOSS), 2022)
This study aims to identify best practices in managing human banking resources in the digital era through scientific evidence. So the next step we took was to complete data from various relevant sources to answer this problem. After collecting more than 100 complications, we found around 70 publication sources that we saw were appropriate for us to use as study support for findings. We conducted data coding and thorough analysis and concluded using a phenomenological approach. Based on the discussion of the results and available data, we can conclude that many strategies have been carried out by banks in this digital era, including establishing partnerships with other parties, providing appropriate incentives to staff, responding to real-time data to consumers and banks having a vision for the future. to collaborate for development and progress. It is hoped that these findings will be helpful in other studies.